A novel modified hanging maneuver in laparoscopic left hemihepatectomy. (2020) - Takagi, Kosei; Umeda, Yuzo; Kuise, Takashi; Yoshida, Ryuichi; Yoshida, Kazuhiro; Yasui, Kazuya; Tani, Yuma; Yagi, Takahito; Fujiwara, Toshiyoshi
Highlights: The liver hanging maneuver is an essential technique in open hepatectomy. Few studies have reported on use of hanging maneuver in laparoscopic hepatectomy. We have developed a novel modified laparoscopic hanging maneuver technique. This novel modified hanging maneuver is easy and reproducible to use. Abstract: Introduction: The liver hanging maneuver is an essential technique for controlling bleeding in hepatectomy, however it is often difficult in laparoscopic major hepatectomy. The present study describes a novel modified hanging maneuver in laparoscopic left hemihepatectomy. Presentation of case: A 29-year-old female underwent laparoscopic left hemihepatectomy for mucinous cystic neoplasm. After mobilizing the left lobe, the liver parenchyma was dissected along the demarcation line. For the hanging technique, the upper edge of the hanging tape was placed on the lateral side of the left hepatic vein, and fixed with the Falciform ligament. The lower edge of the tape was extracted outside the abdomen. Accordingly the hanging tape can be controlled extraperitoneally during the liver parenchyma dissection. Discussion: This technique includes several advantages including no need of assistance using forceps, easy control of the hanging tape extraperitoneally, outflow control, better exposure of surgical field, and helpful guide of the liver dissection line toward the root of the left hepatic vein. Conclusion: Our novel modified hanging maneuver is easy and reproducible to use in laparoscopic left hemihepatectomy. Moreover, this technique can be applied to other laparoscopic hepatectomy.